2018
DOI: 10.1002/adts.201800021
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical–Thermal Evaluation of an Integrated Thermal Management System for Lithium‐Ion Battery Modules

Abstract: Thermal management of lithium-ion (Li-ion) batteries using phase change materials (PCM) demonstrate advantages such as compactness and reduced weight compared to conventional active cooling systems. However, the heat accumulation in PCM due to ineffective cooling and added thermal inertia may lead to thermal management system failure. In this study, a hybrid active-passive thermal management system for a Li-ion battery module is presented. Graphite nanopowder and highly oriented pyrolytic graphite sheets are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A streamlined electrochemical‐thermal coupled model is developed. The impact of nanoparticle mass fraction, PCM thickness, and air inlet temperature under a driving cycle are investigated and observed that a safe and better thermal uniformity was obtained with hybrid BTMS 104 …”
Section: Recent Work Related To Organic and Inorganic Pcms With Heat ...mentioning
confidence: 99%
“…A streamlined electrochemical‐thermal coupled model is developed. The impact of nanoparticle mass fraction, PCM thickness, and air inlet temperature under a driving cycle are investigated and observed that a safe and better thermal uniformity was obtained with hybrid BTMS 104 …”
Section: Recent Work Related To Organic and Inorganic Pcms With Heat ...mentioning
confidence: 99%
“…The main drawback of PCMs, such as paraffin, is the low thermal conductivity, which goes against heat dissipation and absorption. [ 177 , 178 ] One promising solution to this drawback is the addition of expanded graphite, graphene or metals to PCMs to improve their thermal conductivity. [ 179 ] Compared to paraffin, more cost‐effective sodium thiosulfate pentahydrates (STP) are advantageous in higher thermal conductivity and an appropriate melting point (47 °C) within desired battery operating temperature range.…”
Section: Thermal Management Of Aibsmentioning
confidence: 99%
“…Driven by the miniaturization and integration of electronic equipment and devices, heat accumulation rises dramatically due to ultrahigh energy density, , reducing electronic components’ reliability, working lifetime, and safety. Therefore, how to effectively manage heat is a crucial issue for modern devices. Thermally conductive materials play a decisive role in thermal management .…”
Section: Introductionmentioning
confidence: 99%